De novo ALX4 variant detected in child with non-syndromic craniosynostosis - Fonteles,C.S. (2021)
Current understanding of the genetic factors contributing to the etiology of non-syndromic craniosynostosis (NSC) remains scarce. The present work investigated the presence of variants in ALX4, EFNA4, and TWIST1 genes in children with NSC to verify if variants within these genes may contribute to the occurrence of these abnormal phenotypes. A total of 101 children (aged 45.07±40.94 months) with NSC participated in this cross-sectional study. Parents and siblings of the probands were invited to participate. Medical and family history of craniosynostosis were documented. Biological samples were collected to obtain genomic DNA. Coding exons of human TWIST1, ALX4, and EFNA4 genes were amplified by polymerase chain reaction and Sanger sequenced. Five missense variants were identified in ALX4 in children with bilateral coronal, sagittal, and metopic synostosis. A de novo ALX4 variant, c.799G>A: p.Ala267Thr, was identified in a proband with sagittal synostosis. Three missense variants were identified in the EFNA4 gene in children with metopic and sagittal synostosis. A TWIST1 variant occurred in a child with unilateral coronal synostosis. Variants were predicted to be among the 0.1% (TWIST1, c.380C>A: p. Ala127Glu) and 1% (ALX4, c.769C>T: p.Arg257Cys, c.799G>A: p.Ala267Thr, c.929G>A: p.Gly310Asp; EFNA4, c.178C>T: p.His60Tyr, C.283A>G: p.Lys95Glu, c.349C>A: Pro117Thr) most deleterious variants in the human genome. With the exception of ALX4, c.799G>A: p.Ala267Thr, all other variants were present in at least one non-affected family member, suggesting incomplete penetrance. Thus, these variants may contribute to the development of craniosynostosis, and should not be discarded as potential candidate genes in the diagnosis of this condition.